A new species of Protrellus Cobb, 1920 (Nematoda, Thelastomatidae) parasite of the field cockroach Blatella vaga Hebard, 1919 (Blattodea, Blattidae) from Catamarca, Argentina - Camino, Nora Beatriz (2013)
A new species of the genus Protrellus, P. blatta sp. nov. parasitizing a field cockroach Blatella vaga Hebard, 1919, from El Tala river, Catamarca, Argentina, is described and illustrated. It is characterized by having the mouth opening circular, the buccal capsule with eight very small teeth, the nerve ring around oesophageal corpus, the excretory pore anterior to vulva, the vulva anterior to base of oesophagus, didelphic, the posterior ovary reflexed anterior to rectum, about one third of a body length from posterior end, the egg ellipsoidal, colourless, bearing a lateral cuticular crest, tail conical, with long filiform projection, the male with testis single, outstretched, one spicule, very small, short and straight, gubernaculums absent, the genital papillae arranged in three pairs of ventrolateral papillae, of which the first pair are close together and preanal position, two pairs postanal, tail conical and short, less than one twentieth of total body. A taxonomic key of Protrellus species is given.